The Concept of Sharia Compliance on Islamic Bank Murabaha Financing in the Maqashid Sharia Approach: A Theoretical Study - Faizin, Nurul; Djayusman, Royyan Ramdhani (AL-IKTISAB: Journal of Islamic Economic Law, 2023)
••• English ••• Murabaha financing is the financing with the highest value in Indonesia which can be seen from the Islamic Banking Snapshot issued by OJK, which shows that the murabaha financing using covers 46,22% of all distributed financing until September 2021. This research aims to give the theoretical background for sharia compliance murabaha bank financing, which gives an understanding of how Islamic banks can be sharia compliance in financing using the murabaha contract. This research is descriptive qualitative research in the form of literature research using theoretical or conceptual study methodology. The result shows the sharia compliance of murabaha financing is based on four approaches, namely the ‘aqd approach, maqashid sharia approach, the documentation approach, and the accounting and financial reporting approach. The ‘aqd approach states that the murabaha transaction should be bonafide among independent parties (supplier, buyer, and financier) and not involve a guaranteed profit. As for the maqasid sharia approach, besides ensuring maqasid sharia in wealth (its circulation, its clarity, its preservation, its stability, and justice in it), the murabaha should ensure public interest as well as to contribute to the removal of hardship. In the documentation approach, the form and the materials of the contract documented for murabaha should comply with the principle and requirements of the contract according to Islamic law and has to be overseen by the Sharia Supervisory Board in drafting. And for the accounting and financial reporting approach, the information disclosure should contain the value of assets when executing the murabaha, clarifications that murabaha receivables are measured on the cost, the profits of murabaha were completed when contracting, the deferred profit is not deducted from the murabaha receivable, there is no clear treatment for early repayment if it occurs, and there is no clear handling of cases of customer insolvency or delay in payment if any. ••• Indonesian ••• Pembiayaan murabahah merupakan pembiayaan dengan nilai tertinggi di Indonesia yang dapat dilihat dari Snapshot Perbankan Syariah yang diterbitkan oleh OJK, yang menunjukkan bahwa pembiayaan murabahah mencakup 46,22% dari seluruh pembiayaan yang didistribusikan hingga September 2021. Penelitian ini bertujuan untuk memberikan landasan teoritis kepatuhan kepada syariah untuk pembiayaan murabahah di perbankan syariah, yang memberikan pemahaman tentang bagaimana bank syariah dapat mematuhi syariah dalam menyalurkan pembiayaan menggunakan akad murabahah. Penelitian ini merupakan penelitian kualitatif deskriptif dalam bentuk penelitian kepustakaan menggunakan metodologi kajian teoritis atau konseptual. Hasil penelitian menunjukkan kepatuhan syariah pembiayaan murabahah didasarkan pada empat pendekatan, yaitu pendekatan akad, pendekatan maqashid syariah, pendekatan dokumentasi, dan pendekatan akuntansi dan laporan keuangan. Pendekatan akad menyatakan bahwa transaksi murabahah harus bonafide di antara pihak independen (pemasok, pembeli, dan pemberi pembiayaan) dan tidak melibatkan keuntungan terjamin. Adapun pendekatan maqashid syariah, selain memastikan maqashid syariah dalam harta (peredarannya, kejelasannya, pelestariannya, stabilitasnya, dan keadilan di dalamnya), murabahah harus memastikan kepentingan umum serta berkontribusi pada penghapusan kesulitan. Dalam pendekatan dokumentasi, bentuk dan isi kontrak yang didokumentasikan untuk murabahah harus sesuai dengan prinsip dan persyaratan kontrak menurut hukum Islam dan harus diawasi oleh Dewan Pengawas Syariah dalam penyusunannya. Dan untuk pendekatan akuntansi dan pelaporan keuangan, keterbukaan informasi harus berisi nilai aset saat melaksanakan murabahah, klarifikasi bahwa piutang murabahah diukur menurut biaya, keuntungan murabahah ditetapkan saat kontrak, laba tangguhan tidak dikurangkan dari piutang murabahah, tidak ada perlakuan yang jelas untuk pelunasan awal jika terjadi, dan tidak ada penanganan yang jelas atas kasus kepailitan pelanggan atau keterlambatan pembayaran jika ada.